Magnets and electricity - Jennings, Terry (Oxford Universty Press Karachi, 1993)
This volume is part of a complete science resource/programme for primary schools. Each pupils' book has been designed to introduce young readers to scientific information in a straightforward and easily accessible way. Concepts are presented through controlled and integrated words and images.